2019
DOI: 10.2106/jbjs.rvw.18.00026
|View full text |Cite
|
Sign up to set email alerts
|

Gap Balancing, Measured Resection, and Kinematic Alignment

Abstract: Although total knee arthroplasty is a successful and well-established surgical intervention, there is renewed interest in evaluating its theoretical underpinning and surgical techniques in order to identify areas for potential improvement in patient outcomes.» The practice of using mechanical limb alignment for total knee arthroplasty arose from the design of the modern condylar knee prosthesis, with the goal of equally distributing stresses across the articulating surfaces of the prosthesis. Disclosure: No ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 44 publications
1
24
0
3
Order By: Relevance
“…Balancing in extension first, as was done in our study, was considered more reliable, as releases were more precise [10]. Although surgical procedures to achieve this should follow a systematised and progressive order [1,11] STR increases the complexity of the procedure [12], so a correct alternative would be to do it only if necessary, knowing this could be helpful in pre-operative planning. A tool for objective quantification of the femorotibial space, resulting from limb alignment and the manoeuvre performed [13,14] was CAS.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Balancing in extension first, as was done in our study, was considered more reliable, as releases were more precise [10]. Although surgical procedures to achieve this should follow a systematised and progressive order [1,11] STR increases the complexity of the procedure [12], so a correct alternative would be to do it only if necessary, knowing this could be helpful in pre-operative planning. A tool for objective quantification of the femorotibial space, resulting from limb alignment and the manoeuvre performed [13,14] was CAS.…”
Section: Discussionmentioning
confidence: 75%
“…The objective of the total knee replacement (TKR) is to achieve a well-aligned and well-balanced knee [1]. Creation of symmetric balanced flexion and extension gaps (difference less than 3 mm) is a surgical goal of a TKR, which often requires a soft tissue release (STR) at the time of implantation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Different authors investigated the outcome of total knee arthroplasty (TKA) and demonstrated that up to 20% of the patients are not satisfied with their knee function after TKA [ 4 , 9 , 10 , 13 , 20 ] Pain, instability, and limitation of the range of motion are the most commonly reported symptoms among unsatisfied patients, while the major causes reported of unsuccessful TKA are inadequate alignment and errors in balancing [ 4 , 9 ]. With the aim of improving outcomes, there is an increasing focus on different alignment options [ 17 ] and soft-tissue balancing techniques [ 18 ]. As standard instrumentations might not be accurate enough to achieve either of these, balancing tools, patient-specific instrumentations (PSI) and, more recently, computer and robotic-assisted TKA have been introduced to help surgeons to adopt hybrid techniques and, at the same time, to optimize alignment, reducing the number of outliers [ 6 , 13 , 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precise positioning and alignment of the prosthesis in the coronal and sagittal planes and the balance of the soft tissues are critical to the recovery of function after TKA [ 5 , 6 ]. Gap balancing (GB) and measured resection (MR) are two different surgical techniques that can be used to achieve this goal [ 5 , 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MR technique uses anatomical markers such as the transepicondylar axis (TEA), anteroposterior (AP) axis, or the posterior condylar axis (PCA) to determine the rotation of the femoral prosthesis [ 5 , 7 , 11 ]. However, some researchers have shown that MR technology has great variability in setting the rotation of the femoral components due to individual differences in anatomical landmarks [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%